Preparation method and application of battery-grade iron phosphate

During the preparation process of lithium iron phosphate, titanium dioxide is added to the solution to allow titanium elements to enter the crystal lattice of FePO4, which solves the problem of difficulty in titanium doping and poor electrochemical performance, and achieves efficient titanium doping and electrochemical performance improvement.

CN119637823APending Publication Date: 2025-03-18FUJIAN INST OF RES ON THE STRUCTURE OF MATTER CHINESE ACAD OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411553813.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The existing titanium doping technology of lithium iron phosphate is difficult to effectively integrate into the crystal lattice of lithium iron phosphate, resulting in high doping difficulty and unsatisfactory particle morphology, which in turn affects electrochemical performance.

Method used

Titanium dioxide is added to the solution containing iron red, ferric chloride and phosphoric acid. With the formation of FePO4·2H2O, the titanium element enters the crystal lattice of FePO4, and the preparation of battery-grade titanium doped iron phosphate is completed by high-temperature calcination.

Benefits of technology

It realizes effective doping of titanium elements, improves the electrochemical performance of lithium iron phosphate, and has a simple process, high purity of products, and is environmentally friendly and economical.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119637823A_ABST
    Figure CN119637823A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of battery-grade iron phosphate, and belongs to the field of new energy materials. The preparation method of the battery-grade iron phosphate comprises the following steps: mixing iron oxide red, ferric chloride, phosphoric acid and water, putting the mixture into a closed container, reacting, separating the reacted product to obtain filtrate and a filter cake, and drying and calcining the filter cake to obtain the battery-grade iron phosphate. During mixing, titanium dioxide can be added. Iron oxide red is used as an iron source and a neutralizer to neutralize acidity of phosphoric acid and promote generation of iron phosphate; no other impurity ions enter, and the product purity is high; the filtrate can be recycled, no wastewater is discharged, and the method is economical and environment-friendly; the Ti element doping process is simple, the form obtained after doping is granular, and the electrochemical performance of lithium iron phosphate can be effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a preparation method and application of battery-grade iron phosphate, and belongs to the field of new energy materials. Background Art

[0002] Ferric phosphate is an important raw material for the production of lithium iron phosphate. At present, the phosphoric acid preparation process can be roughly divided into two types: "sodium method" and "iron method". The "sodium method" is to use sodium hydroxide as liquid alkali, ferrous sulfate as iron source, and phosphoric acid as phosphorus source to neutralize and prepare hydrated ferric phosphate, and then calcine to obtain ferric phosphate. This process has cost advantages, but the sodium ion content in ferric phosphate is high, and the by-product sodium sulfate is difficult to handle and has low value; the "iron method" is that iron powder directly reacts with phosphoric acid to produce hydrogen and generate ferrous ions, and then adds an oxidant, such as hydrogen peroxide, to convert it into hydrated ferric phosphate, and then calcines to obtain ferric phosphate. This process has high product purity and simple operation, but the cost is high, a large amount of hydrogen is produced during the reaction process, and the safety is poor.

[0003] In addition, doping with titanium is an effective way to improve the performance of lithium iron phosphate positive electrode materials, but the titanium doping technology of lithium iron phosphate tends to be carried out in the synthesis stage. However, due to the extremely high melting point of titanium dioxide, it is difficult to smoothly integrate it into the lattice of lithium iron phosphate. This technical obstacle not only increases the difficulty of doping, but may also lead to unsatisfactory particle morphology after doping, which in turn has an adverse effect on the natural growth process of lithium iron phosphate primary particles. Ultimately, these unfavorable factors accumulated and failed to effectively improve the electrochemical performance of lithium iron phosphate as expected, becoming a key issue that needs to be urgently solved in current technological exploration. Summary of the invention

[0004] Based on the above-mentioned technical problems, the present application proposes to add an appropriate amount of titanium dioxide into a solution containing red iron oxide (iron oxide), ferric chloride and phosphoric acid (phosphorus source), wherein the red iron oxide serves as an iron source and neutralizing agent for preparing iron phosphate, neutralizes the acidity of phosphoric acid, promotes the combination of iron and phosphate, and generates hydrated iron phosphate (FePO4·2H2O), and titanium dioxide is directly added to the reaction raw materials, which will be accompanied by the generation of FePO4·2H2O, followed by high-temperature calcination, and the Ti element enters the FePO4 lattice to complete the preparation of battery-grade titanium-doped iron phosphate.

[0005] According to a first aspect of the present application, a method for preparing battery-grade iron phosphate is provided.

[0006] A method for preparing battery-grade iron phosphate comprises the following steps:

[0007] Iron oxide red, ferric chloride, phosphoric acid and water are mixed and placed in a sealed container for reaction. The reaction product is separated to obtain a filtrate and a filter cake. The filter cake is dried and calcined to obtain the battery-grade iron phosphate.

[0008] Optionally, in the raw material, the molar ratio of iron element to phosphorus element is 1:1.0-2.0;

[0009] The molar number of iron is calculated based on the total iron contained in iron oxide red and ferric chloride;

[0010] The molar number of phosphorus is calculated based on the phosphorus contained in phosphoric acid;

[0011] The molar ratio of iron oxide red to ferric chloride is 1:4-8.

[0012] Optionally, the molar ratio of iron element to phosphorus element is independently selected from any value of 1:1.0, 1:1.1, 1:1.2, 1:1.3, 1:1.4, 1:1.5, 1:1.6, 1:1.7, 1:1.8, 1:1.9, 1:2.0 or any range between two thereof.

[0013] Optionally, the molar ratio of iron oxide red to ferric chloride is independently selected from any value of 1:4, 1:4.5, 1:5, 1:5.5, 1:6, 1:6.5, 1:7, 1:7.5, 1:8, or any range between two values.

[0014] Optionally, in the raw material, the solid-liquid mass ratio is 1:8 to 20;

[0015] Among them, the solid mass is calculated as the total mass of iron red and ferric chloride;

[0016] The mass of the liquid is calculated as the total mass of phosphoric acid and water.

[0017] Optionally, the solid-liquid mass ratio is independently selected from any value among 1:8, 1:10, 1:12, 1:14, 1:16, 1:18, 1:20, or any range value between two of them.

[0018] Optionally, titanium dioxide is added during mixing;

[0019] The molar ratio of iron element to titanium element is 1:0-0.2;

[0020] The molar number of iron is calculated based on the total iron contained in iron oxide red and ferric chloride;

[0021] The molar number of titanium element is calculated based on the titanium element contained in titanium dioxide.

[0022] Optionally, the molar ratio of the iron element to the titanium element is independently selected from any value of 1:0, 1:0.02, 1:0.05, 1:0.07, 1:0.1, 1:0.12, 1:0.15, 1:0.17, 1:0.2, or any range between the two.

[0023] When the amount of titanium dioxide added is 0, it is undoped battery-grade iron phosphate; when the amount of titanium dioxide added is greater than 0, it is battery-grade titanium-doped iron phosphate.

[0024] Optionally, the reaction conditions are: the reaction temperature is 90 to 105° C., and the reaction time is 24 to 96 hours.

[0025] Optionally, the reaction temperature is independently selected from any value of 90°C, 92°C, 95°C, 97°C, 100°C, 102°C, 105°C, or any range therebetween.

[0026] Optionally, the reaction time is independently selected from any value among 24 h, 36 h, 48 h, 60 h, 72 h, 84 h, 96 h, or any range therebetween.

[0027] Optionally, the calcination conditions are: the calcination temperature is 400 to 900° C., and the calcination time is 1 to 12 hours.

[0028] Optionally, the calcination temperature is independently selected from any value of 400°C, 450°C, 500°C, 550°C, 600°C, 650°C, 700°C, 750°C, 800°C, 850°C, 900°C, or any range therebetween.

[0029] Optionally, the calcination time is independently selected from any value of 1 h, 2 h, 4 h, 5 h, 6 h, 8 h, 10 h, 12 h, or any range therebetween.

[0030] Optionally, the filtrate is recycled as a raw material. After the reaction is completed, the filtrate is filtered and washed, and the filtrate is recycled to the front as a raw material to replenish the iron source and phosphorus source and continue to be used.

[0031] As a preferred embodiment, the method for preparing battery-grade iron phosphate comprises the following steps:

[0032] (1) Iron oxide red, ferric chloride, phosphoric acid and titanium dioxide are directly heated into a reaction container, wherein the molar ratio of iron to phosphorus is 1:1.0-2.0, and the molar ratio of iron oxide red to ferric chloride is 1:4-8. The molar ratio of iron to titanium is 1:0-0.2, and when the molar ratio of titanium dioxide is 0, it is undoped iron phosphate.

[0033] (2) The solid-liquid mass ratio is 1:8-20, the reaction temperature is 90-105°C, rapid stirring, and the reaction time is 24h-96h.

[0034] (3) You can see the color gradually changing from red to golden yellow.

[0035] (4) After the reaction is completed, filter and wash, and recycle the filtrate to the front as raw material to replenish the iron source and phosphorus source for further use.

[0036] (5) After drying the filter cake, calcining it in air at a calcination temperature of 400-900° C. can obtain battery-grade titanium-doped iron phosphate.

[0037] According to a second aspect of the present application, there is provided an application of battery-grade iron phosphate obtained by the preparation method as a positive electrode material.

[0038] The battery-grade iron phosphate obtained by the preparation method described above is used as a positive electrode material.

[0039] The beneficial effects of this application include:

[0040] The preparation method of battery-grade iron phosphate provided in the present application utilizes iron red as an iron source and a neutralizing agent to neutralize the acidity of phosphoric acid and promote the formation of iron phosphate; no other impurity ions enter, and the product purity is high; the filtrate can be recycled and reused, and there is no wastewater discharge, which is economical and environmentally friendly; the Ti element doping process is simple, and the form obtained after doping is granular, which can effectively improve the electrochemical properties of lithium iron phosphate. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 Flow chart for preparing battery grade iron phosphate.

[0042] Figure 2 This is a scanning electron microscope (SEM) image of the battery-grade iron phosphate prepared in Example 1, with a scale of 1 μm.

[0043] Figure 3 This is the phase structure spectrum (XRD) of the battery-grade iron phosphate prepared in Example 1.

[0044] Figure 4 This is a scanning electron microscope (SEM) image of the battery-grade titanium-doped iron phosphate prepared in Example 2, with a scale of 1 μm.

[0045] Figure 5 This is the phase structure spectrum (XRD) of the battery-grade titanium-doped iron phosphate prepared in Example 2.

[0046] Figure 6 This is the element distribution diagram of the battery-grade titanium-doped iron phosphate prepared in Example 2.

[0047] Figure 7 The charge and discharge cycle stability diagram obtained by testing the products obtained in Example 1 and Example 2 is prepared into lithium iron phosphate materials as raw materials. DETAILED DESCRIPTION

[0048] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.

[0049] Unless otherwise specified, the raw materials in the examples of this application were purchased through commercial channels.

[0050] Unless otherwise specified, conventional methods were used for testing and instrument settings were those recommended by the manufacturer.

[0051] The analysis method in the examples of this application is as follows:

[0052] The scanning electron microscope (SEM) analysis was performed using a SU-8010 field emission scanning electron microscope with an elemental analysis probe.

[0053] The instrument used for phase structure (XRD) analysis is MiniFlex II.

[0054] like Figure 1 As shown, it is a flow chart for preparing battery-grade iron phosphate. Iron oxide red, ferric chloride, phosphoric acid, titanium dioxide and water are mixed and put into a reactor. The mixture is reacted under heating and stirring to obtain hydrated iron phosphate and waste liquid containing phosphoric acid and ferric chloride. The waste liquid is recycled. The hydrated iron phosphate is calcined to obtain battery-grade iron phosphate / battery-grade titanium-doped iron phosphate.

[0055] Example 1

[0056] 319g of iron oxide red, 917g of ferric chloride, 1384g of 85% phosphoric acid and 8000mL of pure water were added to the reactor. The molar ratio of iron element to phosphorus element was 1:1.2, the molar ratio of iron oxide red to ferric chloride was 1:4, and the solid-liquid mass ratio was 1:9. The reaction was carried out under rapid stirring at a reaction temperature of 101°C and a reaction time of 72h. The color in the reactor changed from red to golden yellow.

[0057] After filtering, a filter cake is obtained, which is dried and calcined at a temperature of 800° C. for 1 h, and then cooled naturally to obtain battery-grade iron phosphate.

[0058] Example 2

[0059] 319g of iron oxide red, 917g of ferric chloride, 1384g of 85% phosphoric acid, 8000mL of pure water, and 20g of titanium dioxide were added to the reactor. The molar ratio of iron to phosphorus was 1:1.2, the molar ratio of iron oxide red to ferric chloride was 1:4, the molar ratio of iron to titanium was 1:0.03, and the solid-liquid mass ratio was 1:9. The reaction was carried out under rapid stirring at a reaction temperature of 101°C and a reaction time of 72h. The color in the reactor changed from red to golden yellow.

[0060] After filtering, a filter cake is obtained, which is dried and calcined at a temperature of 800° C. for 1 h. After natural cooling, battery-grade titanium-doped iron phosphate is obtained.

[0061] Example 3

[0062] 319g of iron oxide red, 917g of ferric chloride, 1384g of 85% phosphoric acid, 8000mL of pure water, and 40g of titanium dioxide were added to the reactor. The molar ratio of iron to phosphorus was 1:1.2, the molar ratio of iron oxide red to ferric chloride was 1:4, the molar ratio of iron to titanium was 1:0.03, and the solid-liquid mass ratio was 1:9. The reaction was carried out under rapid stirring at a reaction temperature of 101°C and a reaction time of 72h. The color in the reactor changed from red to golden yellow.

[0063] After filtering, a filter cake is obtained, which is dried and calcined at a temperature of 800° C. for 1 h. After natural cooling, battery-grade titanium-doped iron phosphate is obtained.

[0064] Example 4

[0065] The operation is the same as that of Example 2, except that the solid-liquid mass ratio is changed to 1:10 to obtain battery-grade titanium-doped iron phosphate.

[0066] Example 5

[0067] The operation is the same as in Example 2, except that the reaction temperature is changed to 95° C. to obtain battery-grade titanium-doped iron phosphate.

[0068] Example 6

[0069] The operation is the same as in Example 2, except that the reaction time is changed to 96 hours to obtain battery-grade titanium-doped iron phosphate.

[0070] Example 7

[0071] The operation is the same as that of Example 2, except that the calcination temperature is changed to 400° C. to obtain battery-grade titanium-doped iron phosphate.

[0072] Example 8

[0073] The operation is the same as in Example 2, except that the calcination time is changed to 12 h to obtain battery-grade titanium-doped iron phosphate.

[0074] The samples prepared in the above examples were analyzed.

[0075] Example 1 The scanning electron microscope image (SEM) of battery-grade iron phosphate obtained is as follows Figure 2 As shown in Figure 2, it can be seen that the prepared battery-grade iron phosphate is lamellar; its XRD spectrum is as follows Figure 3 As shown, it can be seen that the phase is a standard FePO4 structure without other impurities.

[0076] The battery-grade titanium-doped iron phosphate obtained in Examples 2 to 8 was analyzed, with the sample obtained in Example 2 being used as a typical example. The scanning electron microscope (SEM) image thereof is shown as follows: Figure 4As shown in FIG. 1 , it can be seen that the prepared battery-grade iron phosphate becomes granular; its XRD spectrum is as follows Figure 5 As shown, it can be seen that the physical phase is a standard FePO4 structure without other impurities. By refining the XRD pattern and calculating the unit cell parameters as shown in Table 1, the unit cell parameters after titanium doping (Example 2) are larger than those before doping (Example 1), indicating that the Ti element is doped into the FePO4 lattice.

[0077] Table 1 Changes in unit cell parameters before and after titanium doping

[0078]

[0079] The element distribution analysis of the battery-grade titanium-doped iron phosphate obtained in Example 2 is as follows: Figure 6 As shown, it can be seen that within the element surface distribution area, the Fe element is evenly distributed and the Ti element is dispersedly distributed. The main reason is that the titanium content is very small. In the calculation example, the molar ratio of the Fe element to the Ti element is 1:0.03.

[0080] The products obtained in Example 1 and Example 2 were mixed with lithium carbonate and glucose, respectively, and calcined under a protective atmosphere to obtain the corresponding lithium iron phosphate. The charge and discharge cycle stability thereof was tested, respectively. Figure 7 As shown, it can be seen that the cycle stability of both is good. The overall capacity of Example 2 is higher than that of Example 1. Ti doping increases the capacity of lithium iron phosphate and improves the cycle stability.

[0081] Comparative Example 1

[0082] The sodium method is used to prepare ferric phosphate. The specific process is as follows: ferric chloride and phosphoric acid solution are mixed, wherein the Fe:P molar ratio is 1:1.1, and a 1M FeCl3 and 1.1M H3PO4 mixed solution is prepared as an acidic solution. At this time, the pH of the acidic solution is -0.8. An appropriate amount of H2O2 is added to oxidize a small amount of Fe 2+ . In addition, the alkaline solution is 1M NaOH, and the pH is 13.5. As shown, the inflow of the acid and alkali solution is controlled to ensure that the pH is between 0 and 1, and the reaction temperature is set at 80°C. Solid-liquid separation, calcination at 800°C, to obtain iron phosphate. Table 2 is the main element content of the products of the comparative example and embodiment 1 tested, and by comparison, it can be seen that the "sodium method" prepares iron phosphate with a high sodium content.

[0083] Table 2 Purity test of battery grade iron phosphate in comparative example 1 and example 1

[0084] plan Purity of iron phosphate Fe / P(mol) Na(ppm) K(ppm) Comparative Example 1 98.5 1.01 100 20 Example 1 99.8 0.99 8 5

[0085] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.

Claims

1. A method for preparing battery-grade iron phosphate, characterized in that: The following steps are involved: Iron oxide red, ferric chloride, phosphoric acid and water are mixed and placed in a sealed container for reaction. The reaction product is separated to obtain a filtrate and a filter cake. The filter cake is dried and calcined to obtain the battery-grade iron phosphate.

2. The preparation method according to claim 1, characterized in that: In the raw materials, the molar ratio of iron to phosphorus is 1:1.0-2.0; The molar number of iron is calculated based on the total iron contained in iron oxide red and ferric chloride; The molar number of phosphorus is calculated based on the phosphorus contained in phosphoric acid; The molar ratio of iron oxide red to ferric chloride is 1:4-8.

3. The preparation method according to claim 1, characterized in that: In the raw materials, the solid-liquid mass ratio is 1:8-20; Among them, the solid mass is calculated as the total mass of iron red and ferric chloride; The mass of the liquid is calculated as the total mass of phosphoric acid and water.

4. The preparation method according to claim 1, characterized in that: While mixing, add titanium dioxide; The molar ratio of iron element to titanium element is 1:0-0.2; The molar number of iron is calculated based on the total iron contained in iron oxide red and ferric chloride; The molar number of titanium element is calculated based on the titanium element contained in titanium dioxide.

5. The preparation method according to claim 1, characterized in that: The reaction conditions are as follows: the reaction temperature is 90-105° C., and the reaction time is 24-96 hours.

6. The preparation method according to claim 1, characterized in that: The calcination conditions are as follows: the calcination temperature is 400-900° C., and the calcination time is 1-12 hours.

7. The preparation method according to claim 1, characterized in that: The filtrate is recycled as raw material.

8. Use of the battery-grade iron phosphate obtained by the preparation method according to any one of claims 1 to 7 as a positive electrode material.